Endocrine adaptations across physical and psychological stressors in long-term space flights. (April 2020) - Angeloni, Debora; Demontis, Gian Carlo
Abstract: The human body needs to adapt to both psychological pressure and physical stressors, such as radiation and microgravity, to cope with the extreme environment represented by a long-term spaceflight. Resolving the relative contributions of physical and psychological stressors and the mechanisms underlying adaptation remains critical for devising effective countermeasures addressing the health and well-being of humans heading to prospective deep-space exploratory-class missions. In the present short review, we discuss recent evidence on the complex role of novel players linking the response to physical and psychological stressors with health-impacting consequences of long-term space flights, such as bone loss and dysregulated immune response.